An old creed for the new South : proslavery ideology and historiography, 1865-1918 - Smith, John David, 1949- (Southern Illinois University Press, 2008)
An Old Creed for the New South: Proslavery Ideology and Historiography, 1865-1918 details the slavery debate from the Civil War through World War I. Award-winning historian John David Smith argues that African American slavery remained a salient metaphor for how Americans interpreted contemporary race relations decades after the Civil War. Smith draws extensively on postwar articles, books, diaries, manuscripts, newspapers, and speeches to counter the belief that debates over slavery ended with emancipation. After the Civil War, Americans in both the North and.